Common corporate tax base (CCTB) and effective tax burdens in the EU member states - Andreas Oestreicher; Timo Reister; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The article assesses the impact of a Common Corporate Tax Base (CCTB) as promoted by the European Commission and the related Working Groups on the effective tax burdens of companies in all 27 EU member states. The results shall help to evaluate the economic consequences of introducing a harmonized set of tax accounting rules for EU-based companies. The proposals for a CCTB covered here include depreciation on intangibles, machinery, buildings, furniture and fixture, simplified valuation of inventories, determination of production costs for stocks, treatment of costs for R&D as part of production costs, provisions for future pension payments, provisions for legal obligations, avoidance of double taxation regarding dividend income, and loss relief. The proposed options for a CCTB are applied for average EU-27 corporations of different size as well as for model companies belonging to different economic sectors.
Keywords: H20; H21; H25; K34; 330; European Taxation; Tax Harmonization; Tax Accounting; Effective Tax Burdens; Körperschaftsteuer; Unternehmensbesteuerung; Steuerbelastung; EU-Steuerrecht; EU-Staaten